State Medical Service - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1943-03-17 1943 1940s 3 pages -3- result of recommendations of past students when subsequently in practice. Opportunities for especial specialist experience is also afforded. Such "plum" appointments should be open to meritorious competition by selection through a special Appointments Board. Ministerial announcements so far on the future of Voluntary Institutions have been most unsatisfactory, tendentiously favourable to their continuance on present private lines, perhaps in view of recent life saving endowments by the deliberate designed policy of generous capitalists turned benefactors. (e) The very best professional skill and advice must be available to every citizen under all conditions and as appropriate to his health needs. This means a reorganisation of specialist services for domiciliary visiting as well as for every type of institution, including rehabilitation centres. Optimum civic health for each and every citizen should be a predominant aim, regardless of the opposition of vested interests. (f) All the ancillary services - maternity, dental, nursing, radiological, pathological - and even including health visitors and welfare workers should be included in the proposed unified co-ordinated health service. (g) All schemes for the handling of special disease, problems such as Tuberculosis, Venereal Disease, Mental Derangements, Industrial Maladies etc. should be similarly co-ordinated. (h) The conditions of service for all the professional workers must be made attractive with stated duty hours, holidays with pay, pensions, with adequate remuneration settled after negotiation with representative medical organisations. Whitley Council machinery should be set up, locally regionally and nationally. 7. In the National Health Service of the future, there should be no clear cut distinction between preventive and curative medicine. Both are different aspects of the same problem. The preventive side is more important but the curative side often has its preventive aspect also. 8. Medical Research - a very important branch - must be brought into the general scheme of the National Health Service and be regarded as properly within the sphere of the Central Health Administration. 9. Special Memoranda will be submitted on special aspects of the National Health Service, such as hospitals and medical institutions, Rehabilitation Centres (not only for the physically disabled but for all classes of medical ailments), National Nutrition and Food, and Industrial Medicine etc. 10. The establishment of Regional bodies for medical purposes will require some consideration of Local Government reform and adjustment, though perhaps the medical issues could best be dealt with by adequate grants under stated conditions from the Central Health administration to Local Authorities. HBM/EM/11.3. 292/847/2/157